Pengaruh Perlakuan Panas Terhadap Sifat Mekanis Dan Struktur Mikro Pada Baja AISI 4340 - Halim Rusjdi; Andika Widya Pramono; Wahyu Bawono Faathir (JURNAL POWERPLANT, 2016)
The heat treatment is a combination of heating and cooling operations to metals or alloys in solid state at a certain time interval detention. This heat treatment is given on the metal or alloy to obtain certain properties. The heat treatment process varies depending on the purpose of the provision of heat treatment itself, which commonly refers to the mechanical properties and microstructure of the material. In this study, we want to know is the effect of heat treatment on mechanical properties and microstructure happened. The heat treatment process is carried out by the method of quenching and tempering method, performed at the beginning of the workpiece AISI4340 and medium carbon steel and mechanical testing is performed tensile test, hardness test rockwell, and testing of microstructure.